The European Political Community and EU Enlargement Policy: Strategic Evasion, Internal Crises, and the Case of Serbia - M. Jovanović, Srđan (International Problems, 2026)
This article examines the European Political Community (EPC) as a mechanism of strategic evasion in the European Union’s enlargement policy. Launched in 2022 in response to Russia’s invasion of Ukraine, the EPC has been framed as a forum to deepen cooperation between EU and non-EU states, with some commentators suggesting it could accelerate accession. This article advances a different interpretation: that the EPC functions as a “holding bay”, designed to manage geopolitical pressure while postponing substantive commitments to enlargement. Drawing on concepts of strategic ambiguity and stabilitocracy, the article situates the EPC within the EU’s broader crisis of coherence. It demonstrates how internal contradictions (ranging from democratic backsliding in Hungary and Poland to the selective tolerance of authoritarianism in Serbia) have undermined the credibility of enlargement conditionality. The EPC institutionalizes this avoidance strategy: by offering visibility without legal obligations, it allows the EU to appear inclusive while deferring contentious debates. The Serbian case illustrates this dynamic most clearly, with Serbia’s authorities benefiting from EPC participation and EU engagement despite authoritarian practices, reinforcing stabilitocracy rather than incentivizing reform. The article concludes that the EPC mirrors the EU’s strategic paralysis: it is less a bridge to integration than a mirror of unresolved internal contradictions, offering short-term stability at the expense of long-term credibility.